2002
DOI: 10.1038/sj.bjc.6600500
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between alcohol dehydrogenase II gene, alcohol consumption, and risk for breast cancer

Abstract: MaeIII Restriction Fragment Length Polymorphism in exon 3 of the alcohol dehydrogenase II was assessed in serum from 467 randomly selected German women and 278 women with invasive breast cancer to evaluate the interaction between a polymorphism of the alcohol dehydrogenase II gene, alcohol consumption and risk for breast cancer. In both groups, usual consumption of different alcoholic beverages was asked for using semiquantitative food frequency questionnaires. We used multivariable logistic regression to sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 36 publications
4
19
0
1
Order By: Relevance
“…Owing to the small number of ADH1B*2 carriers, we were not able to further subdivide the highest alcohol intake category of X12 g day À1 . Corresponding to a previous case-only study (Sturmer et al, 2002), a case-only analysis of our data would yield a statistically significant interaction OR (OR 0.2, 95% CI 0.1 -0.6 for X12 g alcohol day À1 ). However, since ADH1B genotype and alcohol intake are not independent in our study population, the modifying effect of the ADH1B genotype on breast cancer risk associated with alcohol consumption is overestimated in the case-only analysis, partly due to residual confounding by differences in alcohol consumption caused by the genotype (Albert et al, 2001).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Owing to the small number of ADH1B*2 carriers, we were not able to further subdivide the highest alcohol intake category of X12 g day À1 . Corresponding to a previous case-only study (Sturmer et al, 2002), a case-only analysis of our data would yield a statistically significant interaction OR (OR 0.2, 95% CI 0.1 -0.6 for X12 g alcohol day À1 ). However, since ADH1B genotype and alcohol intake are not independent in our study population, the modifying effect of the ADH1B genotype on breast cancer risk associated with alcohol consumption is overestimated in the case-only analysis, partly due to residual confounding by differences in alcohol consumption caused by the genotype (Albert et al, 2001).…”
Section: Discussionsupporting
confidence: 48%
“…Previously, a significant inverse association between the ADH1B*2 allele and frequency of alcohol consumption was observed in a case-only study (Sturmer et al, 2002). We employed a population-based case -control study of women up to age 50 years to examine the potential effect of ADH1B genotype on the association between alcohol consumption and breast cancer risk.…”
mentioning
confidence: 99%
“…One study reported an increased risk of breast cancer among premenopausal, but not postmenopausal, women who were ADH3*1 homozygotes (Freudenheim et al 1999), while another study found no such association (Hines et al 2000). The most recent study found an interaction between the ADH2*2 allele in Caucasian women and alcohol consumption among patients with breast cancer (Sturmer et al 2002). The ADH2*2 allele was more common in the women with breast cancer.…”
Section: Alcohol Dehydrogenasementioning
confidence: 99%
“…88,[92][93][94][95][96][97] However, other studies identified ADH1B*2 as a risk factor. Sturmer et al 98 found that ADH1B*2 was more common in women with breast cancer, despite the fact that those with ADH1B*2 drank less. However, in Lilla et al, 99 ADH1B*2 was associated with decreased risk of breast cancer as alcohol consumption increased, while ADH1B*1 was associated with increased risk with higher alcohol consumption.…”
Section: -80mentioning
confidence: 99%